In the Shadow of the Sun: Perspectives on Contemporary Native Art - McMaster, Gerald (Papers / Canadian Ethnology Service, 1993)
This volume makes available in English most of the essays written to accompany the Canadian Museum of Civilization's exhibition In the shadow of the sun. Not included from the original German publication are the exhibition catalogue section and the essays by Gisela Hoffmann, Bernadette Driscoll and Elizabeth McLuhan. However, Viviane Gray's article appears in this document for the first time. Complemented by images of contemporary Indian and Inuit art, the book provides an overview of the evolution of contemporary Canadian Native art. Regional styles as well as the styles of individual artists are discussed, and the various subjects, themes and techniques reflected in the works of art are examined
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Reservation X - McMaster, Gerald R. (Goose Lane, 1998)
Catalogue d'une exposition tenue à l'origine au "First People's Hall of the Canadian Museum of Civilization", prise en charge par Gerald McMaster. Publié avec le "Canadian Museum of Civilization
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remix New Modernities in a Post-Indian World - Baker, Joe; McMaster, Gerald (Heard Museum/Natural Museum of American Indian, 2007)
Published in conjunction with the exhibition of the same name, on view at the Heard Museum in Phoenix, Arizona, from October 6, 2007, to April 27, 2008, and at the George Gustav Heye Center, National Museum of the American Indian, in New York, New York, from May 26 through September 30, 2008
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigena: Perspectives Autochtones Contemporaines - Martin, Lee-Ann; McMaster, Gerald (Musée canadien des civilisations, 1992)
Catlogue d'exposition avec plusieurs textes.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé